Source and degradation of plastic debris in the marine environment: A new approach based on carbonyl index and stable isotopes - Pietro Cocozza; Eduardo Di Marcantonio; Claudia Pelosi; Fabrizio Monaci; Massimo Marchesi; Silvia Serranti (Journal of Hazardous Materials, 2026)

Microplastic pollution from pellet spillage: Analysis of the Toconao ship accident along the Spanish and Portuguese coasts - Pietro Cocozza; Vincenzo M. Scarrica; Angela Rizzo; Silvia Serranti; Antonino Staiano; Giuseppe Bonifazi; Giorgio Anfuso (Marine Pollution Bulletin, 2025)

Monitoring of contamination by microplastics on sandy beaches at Vulcano Island (Sicily, Italy) by hyperspectral imaging - Pietro Cocozza; Silvia Serranti; Andrea Setini; Paola Cucuzza; Giuseppe Bonifazi (Environmental Science and Pollution Research, 2024)
In this work, the monitoring and characterization of large microplastics (1–5 mm) collected from sandy beaches of Vulcano Island (Aeolian Islands, Sicily, Italy) were carried out for the first time. Microplastics were sampled from two beaches, “Gelso” and “Sabbie Nere,” in three different time periods. The following characteristics of microplastic samples were assessed: quantity, distribution, categories, color, polymer type, size, and shape parameters. The polymers were identified using hyperspectral imaging, whereas an automatic image analysis approach was employed to determine microplastics’ morphological and morphometrical attributes. Finally, the microplastic diversity integrated index was computed to obtain information on the potential emission sources of microplastics. It was found that the concentration of microplastics varies from 0.27 particles/kg_dw to 1.35 particles/kg_dw with fragment being the main collected category, with minor amount of pellet, foam, film, and filament. The predominant color of microplastics was by far white, followed by blue and yellow. The identified polymers were polyethylene and polypropylene followed by expanded polystyrene, polyamide, polystyrene, and polyethylene terephthalate. The morphological and morphometrical characterization highlighted a large variability for most size and shape parameters. Finally, the Microplastics Diversity Integrated Index results showed average indices compared to the literature, with higher values for the “Gelso” site (0.656), indicating a higher heterogeneity of sources, with respect to “Sabbie Nere” beach (0.530).